Cultural Representations in Indian English Language Teaching Textbooks. (February 2022) - Bose, Priyanka; Gao, Xuesong
Culture plays an integral role in English language teaching (ELT) and is a necessary component of ELT textbooks. This study explores the issue of cultural representation in the reading components of ELT textbooks in India, which has received little attention in ELT research world-wide. By incorporating 10 ELT textbooks from four states, one national board from India, and a sequential mixed-method design, this research is aimed at investigating the cultural representation of the textbook content, characteristics of people in terms of race, gender and nationality, and the depth of the cultural content. While the results have revealed a general domination of cultural representations originating from Britain, including a major proportion of British, Irish, and generally White characters, a significant amount of gender bias, and overall minimal in-depth cultural engagement, there exists wide regional variations. Language teachers may adapt cultural representations that are relevant with other pedagogical resources to engage English language learners in critical pursuits.